Postoperative complications deteriorate long-term outcome in pancreatic cancer patients - Kamphues, Carsten; Bova, Roberta; Stenzinger, Albrecht (Annals of surgical oncology, 2012)
Background Different tumor-specific prognostic factors have been identified in recent years for patients who undergo surgery due to pancreatic head cancer, but the results often were inconsistent. Furthermore, the impact of postoperative complications on patient long-term survival has not been described.MethodsThe long-term outcome of 428 patients who underwent resection of pancreatic head cancer at our center during a 17-year period was evaluated. Perioperative details, including postoperative complications, as well as the follow-up of all patients who left the hospital postoperatively were collected in a prospective database. Univariate and multivariate models were used to identify potential prognostic factors and to evaluate the impact of postoperative complications on long-term survival.Results The median survival was 15.5 months with a postoperative complication rate (grade I-IV) of 32.7%. Independent prognostic significance was detected for grading (P < 0.001), R status (P = 0.001), and lymph node status (P = 0.003). The occurrence of severe postoperative complications (grade III-IV) was associated with a significantly shortened survival (16.5 vs. 12.4 months; P = 0.002) and was identified as an independent prognostic factor (P = 0.002).ConclusionsThis large study demonstrates that severe postoperative complications have a strong impact on the long-term survival of patients with pancreatic head cancer comparable to tumor characteristics, such as lymph node status, grading, or R status. As a result, the improvement of surgical procedures in specialized centers might lead to a survival benefit in these patients.